Parathyroid allotransplantation to treat post-thyroidectomy hypoparathyroidism: A review of case studies. Issue 3 (June 2021) - Parameswaran, R.; Samuel, M.; Satish, R.L.; Kripesh, A.; Moorthy, V.; Vajjhala, R.; Ng, X.L.; Yip, G.W.; Voon, F.C.T.; Chandran, Manju
Abstract: Objective: Symptomatic long-term hypoparathyroidism following thyroid surgery requires an alternative and permanent therapy that would effectively restore parathyroid function and eliminate the need for substitution drug therapy. The aim of this study was to systematically review the literature on the efficacy and safety of parathyroid allotransplantation to treat post-operative hypoparathyroidism. Methods: MEDLINE, Embase, BIOSIS and the Cochrane Library were searched for published articles (from inception of each database to September 30, 2018). A total of 9 studies comprising 146 patients (177 allotransplantations) with post thyroidectomy hypoparathyroidism were identified. Results: Parathyroid tissues used for allotransplant were cultured parathyroid cells, cryopreserved parathyroid cells and encapsulated microspheres. Post-transplant immunosuppression was only reported in three studies, mainly with oral prednisolone for 2 weeks to 6 months. Mean graft survival following allotransplantation was 47% (95% CI 24%–71%) when patients were followed-up to 6 months and 41% (95% CI 2.3%–80%) at 12 months. There was significant unexplained heterogeneity observed between studies in both these groups (I 2  > 50%). Parathyroid hormone (PTH) levels, and serum calcium levels post intervention was not reported in all studies, but available evidence suggests the levels remains higher (PTH level around 12 pg/ml; Ca level around 8 mg/dl) post-allotransplantation for up to 24 months. Conclusions: Long-term benefit and harms of allotransplantation is still unclear due to the clinical and statistical heterogeneity observed among the studies. Therefore, conduct of a well-designed controlled clinical trial in the immediate future on allotransplantation is of paramount importance.